Primary haemangiopericytoma of lung. Issue 1 (January 1974) - Meade, J. B.; Whitwell, F.; Bickford, B. J.; Waddington, J. K. B.
Abstract : Meade, J. B., Whitwell, F., Bickford, B. J., and Waddington, J. K. B. (1974). Thorax, 29, 1-15. Primary haemangiopericytoma of lung. Haemangiopericytoma is a rare neoplasm which may occur at any age and arise in almost any part of the body. At least 247 examples have been reported in the world literature, but only 24 appear to have arisen primarily in the lung. A summary of the features of these cases, collected from the literature, is presented, and four additional cases are described. The tumour may be innocent [ill] malignant, but there are no characteristic clinical or radiological features to distinguish it from other neoplasms of the lung. Because of uncertainty as to diagnosis and prognosis, surgical excision appears to be the treatment of choice. In the whole series of 28 cases, rather more than half (16) were female, and they tended to be older than the male patients. The mortality from recurrence was higher in males than in females (50% compared with 32%). The prognosis in general seems to be best with small, asymptomatic tumours, especially in female patients. A brief account is given of the nature and function of the pericyte. It was originally thought to be a cell of muscular type, but recent research suggests that it is a multipotent cell capable of development into other cell types and having phagocytic properties. It lies in the basement membrane of capillary blood vessels and may have some connection with antibody formation, but its exact function has not yet been elucidated.